(untitled) (Fiep Bulletin - online, 2016)
The physical education, as a field of knowledge, aims to address the culture of body movement. The task of a teacher of Physical Education is delicate because it must match the group’s interests with those with special needs, the most diverse, given the individuality of each of its students. Faced with this task, realizes the increase in the number of students with Down syndrome in schools. Down syndrome is considered one of the most common birth defects of the world’s population, it cognitive impairment is mild to moderate, so the stages of development and major evolutionary milestones are achieved, though at a slower pace. Thus, this study aims to examine how the physical education can interfere as inclusion factor in regular school, in particular, children with Down syndrome. I remember learning difficulties are established when children encounter problems in perceiving, understanding their world and relate to others in this panorama to physical education is a major factor of inclusion, because it can make use of motor coordination, expression and body culture, for cognitive development. In this way it minimizes the differences and offers possibilities for learning and social inclusion.